2014
DOI: 10.1002/jhm.2223
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic differences in the presentation and management of severe bronchiolitis

Abstract: BACKGROUND AND OBJECTIVE:Bronchiolitis is the leading cause of hospitalization for US infants and is associated with increased risk of childhood asthma. Although studies have shown differences in the presentation and management of asthma across race/ethnicity, it is unclear if such differences are present for bronchiolitis. We examined if racial/ethnic differences exist in the presentation and management of severe bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…10 The potential relevance of genetic background to the degree of severity of bronchiolitis is further reinforced by the differences in the rate of RSV hospitalization observed in populations from different racial and ethnic backgrounds living in the same geographic region or country. 11,12 Together, these findings suggest that host genetic factors might likely contribute to the severity of virus-induced bronchiolitis.…”
Section: Introductionmentioning
confidence: 86%
“…10 The potential relevance of genetic background to the degree of severity of bronchiolitis is further reinforced by the differences in the rate of RSV hospitalization observed in populations from different racial and ethnic backgrounds living in the same geographic region or country. 11,12 Together, these findings suggest that host genetic factors might likely contribute to the severity of virus-induced bronchiolitis.…”
Section: Introductionmentioning
confidence: 86%
“…One prior study by Santiago et al looked at racial and ethnic differences in infants admitted for bronchiolitis. 20 Although Hispanic patients did receive more chest x-rays, steroids, and nebulized treatments compared to non-Hispanic patients, their findings were not statistically significant and they did not conduct an analysis on potential differences in management based on language. In contrast, our study only included patients who had the same primary diagnosis of bronchiolitis and we evaluated management differences based on language.…”
Section: Article In Pressmentioning
confidence: 94%
“…The study design, setting, participants, and methods of data collection have been reported previously. 914 Briefly, we conducted this prospective cohort study at 16 sites across 12 US states during the 2007–2010 winter seasons, as part of the Multicenter Airway Research Collaboration (MARC). MARC is a program of the Emergency Medicine Network (EMNet) (www.emnet-usa.org), a collaboration with >225 participating hospitals.…”
Section: Methodsmentioning
confidence: 99%